1/2 - (2/3 × x - 1/3)=2/3
3/x + 5=15%
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(2^3\times x-5^2\times x=2\times\left(5^2+2^2\right)-33\)
\(x\times\left(2^3-5^2\right)=2\times\left(25+4\right)-33\)
\(x\times\left(8-25\right)=2\times29-33\)
\(x\times-17=25\)
\(x=-\dfrac{25}{17}\)
2) \(15\div\left(x+2\right)=\left(3^3+3\right)\div1\)
\(15\div\left(x+2\right)=\left(27+3\right)\div1\)
\(15\div\left(x+2\right)=30\div1\)
\(15\div\left(x+2\right)=30\)
\(x+2=\dfrac{1}{2}\)
\(x=-\dfrac{3}{2}\)
3) \(20\div\left(x+1\right)=\left(5^2+1\right)\div13\)
\(20\div\left(x+1\right)=\left(25+1\right)\div13\)
\(20\div\left(x+1\right)=26\div13\)
\(20\div\left(x+1\right)=2\)
\(x+1=20\div2\)
\(x+1=10\)
\(x=9\)
4) \(320\div\left(x-1\right)=\left(5^3-5^2\right)\div4+15\)
\(320\div\left(x-1\right)=\left(125-25\right)\div4+15\)
\(320\div\left(x-1\right)=100\div4+15\)
\(320\div\left(x-1\right)=25+15\)
\(320\div\left(x-1\right)=40\)
\(x-1=8\)
\(x=9\)
5) \(240\div\left(x-5\right)=2^2\times5^2-20\)
\(240\div\left(x-5\right)=4\times25-20\)
\(240\div\left(x-5\right)=100-20\)
\(240\div\left(x-5\right)=80\)
\(x-5=30\)
\(x=35\)
6) \(70\div\left(x-3\right)=\left(3^4-1\right)\div4-10\)
\(70\div\left(x-3\right)=\left(81-1\right)\div4-10\)
\(70\div\left(x-3\right)=80\div4-10\)
\(70\div\left(x-3\right)=20-10\)
\(70\div\left(x-3\right)=10\)
\(x-3=7\)
\(x=10\)
1: Ta có: \(20-2\left(x+4\right)=4\)
\(\Leftrightarrow2\left(x+4\right)=16\)
\(\Leftrightarrow x+4=8\)
hay x=4
5: Ta có: \(\left(x+1\right)^3=27\)
\(\Leftrightarrow x+1=3\)
hay x=2
c: Ta có: \(\dfrac{2}{5}\cdot\left[\left(\dfrac{3}{5}\right)^2:\left(-\dfrac{1}{5}\right)^2-7\right]\cdot\left(1000\right)^0\cdot\left|-\dfrac{11}{15}\right|\)
\(=\dfrac{2}{5}\cdot\left(\dfrac{9}{25}:\dfrac{1}{25}-7\right)\cdot1\cdot\dfrac{11}{15}\)
\(=\dfrac{2}{5}\cdot\dfrac{11}{15}\cdot2\)
\(=\dfrac{44}{75}\)
1/ \(1+\frac{2}{x-1}+\frac{1}{x+3}=\frac{x^2+2x-7}{x^2+2x-3}\)
ĐKXĐ: \(\hept{\begin{cases}x-1\ne0\\x+3\ne0\end{cases}}\Leftrightarrow\hept{\begin{cases}x\ne1\\x\ne-3\end{cases}}\)
<=> \(1+\frac{2\left(x+3\right)+x-1}{\left(x-1\right)\left(x+3\right)}=\frac{x^2+2x-3-5}{x^2+2x-3}\)
<=> \(1+\frac{2x+6+x-1}{x^2+2x-3}=1-\frac{5}{x^2+2x-3}\)
<=> \(\frac{3x+5}{x^2+2x-3}+\frac{5}{x^2+2x-3}=1-1\)
<=> \(\frac{3x+5}{x^2+2x-3}+\frac{5}{x^2+2x-3}=0\)
<=> \(\frac{3x+10}{x^2+2x-3}=0\)
<=> \(3x+10=0\)
<=> \(x=-\frac{10}{3}\)
4/15 + 1/2
= 8/30 + 15/30
= 23/30
51/9 - 2/3
= 51/9 - 6/9
= 45/9
= 5
3/4 × 15/26
= 45/104
7/3 : 5/14
= 7/3 × 14/5
= 98/15
\(2^3x+5^2x=2.\left(5^2+2^3\right)-33\)
\(8x+25x=2.\left(25+8\right)-33\)
\(8x+25x=2.33-33\)
\(8x+25x=66-33\)
\(8x+25x=33\)
\(x+\left(8+25\right)=33\)
\(x+33=33\)
\(x=0\)
\(15:\left(x+2\right)=\left(3^3+3\right):10\)
\(15:\left(x+2\right)=\left(27+3\right):10\)
\(15:\left(x+2\right)=30:10\)
\(15:\left(x+2\right)=3\)
\(x+2=15:3\)
\(x+2=5\)
\(x=3\)
1)\(\frac{252}{x}=\frac{84}{97}\Rightarrow\)\(\frac{84}{97}=\frac{252}{291}\Rightarrow x=291\)
6) \(\frac{y}{15}=\frac{2}{5}\Rightarrow\frac{2}{5}=\frac{6}{15}\Rightarrow x=6\)
a: \(\dfrac{-8}{3}\cdot\dfrac{15}{24}=\dfrac{-8}{24}\cdot\dfrac{15}{3}=\dfrac{-1}{3}\cdot5=-\dfrac{5}{3}\)
b: \(=\dfrac{3}{4}\cdot\dfrac{1}{-9}=\dfrac{-1}{12}\)
c: \(x=-\dfrac{7}{6}+\dfrac{5}{8}=-\dfrac{13}{24}\)
d: \(x=-\dfrac{14}{25}-\dfrac{3}{4}=\dfrac{-56-75}{100}=\dfrac{-131}{100}\)
1/2-(2/3×x-1/3)=2/3
(2/3×x-1/3)=1/2-1/3
(2/3×x-1/3)=1/6
2/3×x=1/6+1/3
2/3×x=1/2
x=1/2:2/3
x=3/4
vậy x=3/4
3/x+5=15%
3/x+5=3/20
3/x=3/20-5
3/x=-97/20
3×20=x×-97
60=x×-97
x×-97=60
x=60:-97
x=-60/97
vậy x=-60/97
Ta có:\(\frac{1}{2}-\left(\frac{2}{3}\times x-\frac{1}{3}\right)=\frac{2}{3}\Rightarrow\frac{2}{3}\times x-\frac{1}{3}=\frac{1}{2}-\frac{2}{3}\)
\(\Rightarrow\frac{2}{3}\times x-\frac{1}{3}=\frac{-1}{6}\)
\(\Rightarrow\frac{2}{3}\times x=\frac{-1}{6}+\frac{1}{3}\Rightarrow\frac{2}{3}\times x=\frac{1}{6}\Rightarrow x=\frac{1}{6}:\frac{2}{3}=\frac{1}{4}\)
Vậy x=1/4
Ta có:\(\frac{3}{x}+5=15\%\Rightarrow\frac{3}{x}=\frac{3}{20}-5\Rightarrow\frac{3}{x}=\frac{-97}{20}\Rightarrow x=\frac{3}{\frac{-97}{20}}=\frac{-60}{97}\)
Vậy x=-60/97